Role of DNA methylation in regulating inflammatory cytokine expression in neonates with late-onset sepsis - Sankar, Saranya; Maruthai, Kathirvel; Bobby, Zachariah; Adhisivam, Bethou (Frontiers in Immunology, 2026)
BackgroundNeonatal sepsis is a major health issue, particularly in resource-poor areas. This study aimed to assess the role of DNA methylation in regulating the inflammatory cytokine expression in late-onset neonatal sepsis (LOS).MethodologyWe conducted a cross-sectional study comparing neonates with LOS (n=42) before and after 72 hours of antibiotic treatment (n=25) to healthy controls (HC) (n=42). We analysed DNA methylation patterns and inflammatory cytokine expression levels in both groups.ResultsDNA methylation analysis revealed hypomethylation in pro-inflammatory genes and hypermethylation in anti-inflammatory genes in LOS neonates. These patterns were shifted in follow-up group, with significant changes in inflammatory marker levels, including TNF-α, IFN-γ, IL-10, and TGF-β. The gene expression results aligned with the DNA methylation findings, indicating that changes in the expression of inflammatory genes in late-onset neonatal sepsis (LONS) are influenced by DNA methylation. The results were further validated through an analysis of plasma cytokine levels. LOS cases showed elevated pro-inflammatory cytokines and reduced anti-inflammatory cytokines, except IL-10. In the follow-up group, pro-inflammatory cytokine levels decreased, while anti-inflammatory cytokines increased.ConclusionDNA methylation regulates the expression of inflammatory cytokine genes in late-onset neonatal sepsis. Understanding these molecular changes could lead to better diagnostic and therapeutic approaches for managing neonatal sepsis.